2020
DOI: 10.1016/j.ausmj.2020.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Motivations to Create Alternative Consumption Platforms

Abstract: Consumers are participating in alternative consumption channels in increasing numbers, but increasingly they are becoming creators as well as consumers. The triggers and motivations that lead to consumers becoming creators have been explored in this paper, as we examine the motivations for consumers to become initiators of Collaborative or Alternative Consumption platforms. In-depth interviews examined initiators’ experiences and found that unmet needs from existing retail providers triggered the move to creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…Further, Fraiberger and Sundararajan (2015) suggested that the sharing economy is more likely to be accessed by consumers from low-income groups. In terms of psychographic variables, a wide range can be used to understand the generic motivations of the users of a sharing economy (Bajaj et al, 2020), Konus et al, 2008; Sands et al, 2016). An individual's level of innovativeness is one consumer-related variable which is likely to drive sharing behaviour.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Further, Fraiberger and Sundararajan (2015) suggested that the sharing economy is more likely to be accessed by consumers from low-income groups. In terms of psychographic variables, a wide range can be used to understand the generic motivations of the users of a sharing economy (Bajaj et al, 2020), Konus et al, 2008; Sands et al, 2016). An individual's level of innovativeness is one consumer-related variable which is likely to drive sharing behaviour.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For example, the world's largest sharing economy platforms, such as Airbnb and Uber, are commercial. Consequently, users typically do not perform the role of platform operator (e.g., Airbnb) (Bajaj et al, 2020) but perform as one-sided users as either providers or consumers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Platform businesses create repeated opportunities for peer-to-peer interactions including seeking and providing information, customizing offerings, completing transactions, allowing feedback on sellers and buyers, and publishing reviews and word-of-mouth recommendations. Many rating systems are bidirectional, with providers and purchasers rating each other (Jøsang, 2007), effectively making consumers into content creators (Bajaj et al, 2020). These ratings tend to be high and biased (Aral, 2014).…”
Section: Introductionmentioning
confidence: 99%